2009
DOI: 10.2500/ajra.2009.23.3405
|View full text |Cite
|
Sign up to set email alerts
|

Chinook Wind Barosinusitis: An Anatomic Evaluation

Abstract: Chinook winds are a common source of facial pain and pressure. This is the first study to show that sinonasal anatomic variations may be a predisposing factor. Anatomic variants may induce facial pain by blocking the natural sinus ostia, thus preventing adequate pressure equilibrium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Frequency of pneumatized uncinate process has been reported as 1.5–3%. 8,11,12 However, we identified this variant in 11% of subjects. It is difficult to comment on whether our results deviate from the norm, because there is little published data on the prevalence of middle ethmoidal artery or pneumatized uncinate process.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Frequency of pneumatized uncinate process has been reported as 1.5–3%. 8,11,12 However, we identified this variant in 11% of subjects. It is difficult to comment on whether our results deviate from the norm, because there is little published data on the prevalence of middle ethmoidal artery or pneumatized uncinate process.…”
Section: Discussionmentioning
confidence: 69%
“…Although substantial data exists outlining the prevalence of variant sinus anatomy in various populations, 2,8–37 few studies have evaluated correlations between or among them. In a small study of 47 children with chronic sinusitis, Sivasli et al demonstrated weak associations between presence of agger nasi cells and pneumatization of superior turbinate (ST) and MT, presence of large ethmoid bulla and pneumatized ST and secondary MT, and presence of Haller (infraorbital ethmoid) cell and pneumatization of ST. 12…”
mentioning
confidence: 99%
“…An association of sinonasal anatomy and headaches presumably triggered by Chinook winds has been described. 20 The authors concluded that anatomical variations blocking the sinus ostia may prevent equilibration of changes in atmospheric pressure, thus forming a risk factor for these headaches.…”
Section: Discussionmentioning
confidence: 99%
“…The warm wind is theorized to result in an increased concentration of positive ions with rapid ambient pressure changes that can produce barosinusitis. Rudmik et al 7 indicated that several anatomic variants may predispose individuals to Chinook-wind–related barosinusitis. These include the presence of concha bullosa, sphenoethmoidal cells, and large maxillary sinus volumes, which all serve to increase the relative volume of the sinonasal cavity.…”
Section: Pathophysiology and Reported Causes Of Barosinusitismentioning
confidence: 99%
“…In 1965, Flottes 4 reported the first case of diving-related barosinusitis, which occurred in a deep sea diver who was using a self-contained underwater breathing apparatus. Over the past 50 years, additional causes of sinus barotrauma have also been documented and include the use of gaseous general anesthetic agents, 5 hyperbaric oxygen therapy, 6 Chinook wind exposure, 7 prolonged high altitude exposure, 8 automobile travel, 9 submarine decompression, 10 nasal blowing, 11 and vigorous Valsalva maneuver 12 ( Table 1 ).…”
Section: Introduction and History Of Barosinusitismentioning
confidence: 99%